Dihydroergotamine infusion for pediatric refractory headache: A retrospective chart review. Issue 5 (8th June 2021) - Srouji, Rasha; Schenkel, Sara R.; Forbes, Peter; Cahill, Jennifer E.
Abstract: Background: Headaches are a common symptom in children. Children with refractory headaches may be admitted for inpatient treatment with intravenous dihydroergotamine mesylate (DHE). However, very few studies have characterized these patients and their treatment outcomes using validated, self‐reported, pain scales. Objective: The objective of this study was to describe demographic and clinical characteristics of children admitted for DHE infusion, determine DHE treatment outcomes by means of numeric pain scale ratings, and explore associations between treatment outcomes and clinical characteristics. Methods: Retrospective chart review was completed in patients ages 5–21 admitted for DHE infusion from January 2013 to July 2018 at a large, pediatric academic medical center and community‐based satellite center. All primary headache types were included. Results: A total of 200 unique admissions for DHE were available for analysis. Overall, patients were predominantly White (87.5%, 175/200) and female (80.0%, 160/200) with an average age of 15.4 years (SD 2.3). Common comorbidities included obesity (42.0%, 81/193), anxiety (41.0%, 82/200), and depression (20.0%, 40/200). The mean length of stay was 2.4 days (SD 1.10; range 1–8 days). Most headaches (65.0%, 130/200) met the International Classification of Headache Disorders, 3rd edition criteria for migraine, followed by new daily persistent headache (25.5%, 51/200). Mean DHE maximum dose was 5.3 (SD 2.17; range 0.5–14.5 mg) with most patients requiring 3.5–6.5 mg. DHE was typically terminated at six doses (range 1–15). The most frequently reported adverse event was nausea (5.5%, 11/200). There was no difference in pain severity at admission across headache types, with an average baseline pain score of 8.1 (SD 1.6). Posttreatment reduction in pain score was statistically significant (range: −3.2 to −4.9; each p < 0.001) across all headache types. Overall, 84.0% (168/200) of the patients had some improvement in pain. More than half of the patients (53.5%, 107/200) showed at least moderate improvement (≥50.0% reduction in pain score), and 18.0% (36/200) had full headache resolution. Limited patients (16.0%, 32/200) experienced no improvement in pain. Conclusions: Treatment with DHE resulted in at least some improvement for most patients regardless of headache type or number of doses. Clinical trials stratified by headache type and comorbid factors could help clarify treatment algorithms to optimize patient outcomes.